The “NF-ĸB interacting long noncoding RNA” (NKILA) transcript is antisense to cancer-associated gene PMEPA1 [v1; ref status: indexed, http://f1000r.es/5aq] - Johannes M. Dijkstra; David B. Alexander (F1000Research, 2015)
This correspondence concerns a recent publication in Cancer Cell by Liu et al.1 who analyzed a long noncoding RNA (lncRNA) that they designated “NKILA”. Liu et al. found that NKILA (1) is upregulated by immunostimulants, (2) has a promoter with an NF-ĸB binding motif, (3) can bind to the p65 protein of the NF-ĸB transcription factor and then interfere with phosphorylation of IĸBα, and (4) negatively affects functions that involve NF-ĸB pathways.  And, importantly, they found that (5) low NKILA expression in breast cancers is associated with poor patient prognosis.  However, they entirely failed to mention PMEPA1, a gene which runs antisense to NKILA, and the expression of which is associated with several tumors and which encodes a protein that participates in immune pathways. The PMEPA1 locus, including its promoter region, which Liu et al.1 only discuss in regard to NKILA, is highly conserved through evolution.  Our impression is that NKILA emerged only later in evolution, possibly as an additional means of PMEPA1 regulation.  Liu et al., however, only consider direct binding between NKILA and NF-ĸB as the mechanism for their in vivo observations of NKILA function, but do not provide solid evidence for their model.  If in vivo observations by Liu et al. could be explained by NKILA regulation of PMEPA1, it would contribute to the establishment of PMEPA1 as an important topic of cancer research.  We feel that the herein presented discussion is necessary for a correct interpretation of the Liu et al. article.